Records of four species of subfamily Melolonthinae Macleay, 1819 from Malaysia (Scarabaeidae: Coleoptera) - M. A. A., Ali; Adam, Nur Azura; Hwayyiz, Darya; Muhamad Awang, Rita; S., Azman (AkiNik Publications, 2016)
Melolonthinae is the largest subfamily of Scarabaeidae, their larvae are serious soil pests eating roots and adults have strong mouthparts eating leaves and sometimes young fruits. But it is poorly defined and often being a subject of confusion for its inclusion or exclusion at various stages. Therefore, it is always essential to conduct studies regarding their taxonomical description to differentiate the particular species. This study established the current taxonomical status of four species (Schoenherria vervex, Schoenherria hispida, Lepidiota stigma and Lepidiota leai belonging to subfamily Melolonthinae inhabiting the region of Malaysia and scrutinized their functional sense of anatomy to show the results of evolutionary adaptation to their special habitat in the forest of Malaysia. The species primarily for morpho-species study of genera Schoenherria and Lepidiota were selected. The specimens have been identified by comparing with the specimens at Sarawak’s Museum and The Natural History Museum of Sweden. It is expected from this study that in future it will be helpful for understanding to devise control measure to suppress the pest population below significant level.